Podcast and wikis as generation and management tools of knowledge - Checa García, Fernando (Nómadas. Critical Journal of Social and Juridical Sciences, 2017)
The generalization of the Information Society has brought the popularization of technological tools that enable the creation of new knowledge and its rapid transmission to different sectors and groups interested in accessing them. Tools that allow interaction, easy to learn and use, have become powerful transmitters of a culture increasingly democratized and with lower entry barriers. Among these technology platforms and tools is include podcasts and wikis, whose complexity is somewhat less than the massively used social networking but have become firmly established in the collaborative web ecosystem to allow a substantial change in access, creation and transmission of contents of knowledge societies. This paper analyzes the podcasts and wikis and the possibilities offered to organizations and groups to improve their interactions and the new ways of working that open within the social web using this technology.